Exploring Group Creative Music Therapy as a means to promote social skills in six and seven year old children diagnosed with Attention Deficit Hyperactivity Disorder - Oosthuizen, Helen (University of Pretoria, 2017)
Mini Dissertation (MMus)--University of Pretoria, 2016.